Adult diffuse hepatic hemangiomatosis - Neha Bhardwaj; Mayur Parkhi; Manish Kumar; Lileswar Kaman; Suvradeep Mitra (University of São Paulo, 2022)
Diffuse hepatic hemangiomatosis (DHH) is an uncommon vascular lesion, though hemangiomas are the commonest benign tumors of the liver. The etiology is largely unknown to date; however, its association with giant cavernous hemangiomas (GCH) has been reported in the literature. We present herein, the case of a 37-year-old hypothyroid woman with abdominal fullness for 2 months. The contrast-enhanced computed tomography revealed multiple wellencapsulated lesions involving the liver lobes and was diagnosed as giant cavernous hemangiomas. Most of them, except the deep-seated ones, were enucleated. Histopathological examination highlighted the presence of GCH with irregular margin, replacement of hepatic parenchyma, and presence of multiple micro-hemangiomas suggesting the possibility of DHH further substantiated by retrospective radiological assessment. No extrahepatic vascular lesion was noted, and the post-operative recovery and follow-up were uneventful. Adult DHH is an uncommon entity. The diagnosis of DHH and its distinction from GCH are important from the management and prognostic point of view as recurrence, extrahepatic manifestations, features of consumption coagulopathy, and death from the complications are not uncommon.